Cellular associations of pituitary gonadotrophs in a rodent (Lagostomus maximus maximus) with photoperiod-dependent reproduction - Filippa, Veronica Palmira (2012)
The morphological characteristics and percentage of the cellular associations between gonadotrophs (LH- and FSH-secreting cells) and other cellular types were studied in pituitary pars distalis of adult male viscachas (Lagostomus maximus maximus) by double immunohistochemistry using specific anti-bodies to LH, FSH, PRL, GH, ACTH, TSH and S-100 protein (by folliculostellate cells; FSC), during long and short photoperiods. Bihormonal gonadotrophs were observed in ventro-medial and dorsal regions, interspersed between monohormonal gonadotrophs, and their number increased in short photoperiod. LH- and FSH-gonadotrophs were found around lactotrophs, enclosed by somatotrophs in the dorsal region, and associated with irregular corticotrophs. Gonadotrophs and thyrotrophs were associated along blood vessels and follicular structures. The cytoplasmic prolongations of FSC were in contact with both gonadotrophs. The percentage of LH-FSH, LH-ACTH, LH-FSC, FSH-LH, FSH-PRL, FSH-GH, FSH-ACTH, FSH-TSH and FSH-FSC associations decreased, whereas LH-PRL increased in short as compared to long photoperiod. The most abundant associations were LH-GH and LH-TSH during long photoperiod, but LH-GH and LH-PRL during short photoperiod. FSH-GH and FSH-PRL were the most numerous associations, and LH-FSC and FSH-FSC were the less abundant ones in both photoperiods. These results provide the morphological evidence for specific cellular associations between gonadotrophs and other cellular types of viscacha pituitary.